CLINICAL AND EXPERIMENTAL STUDY OF THE EFFECTS OF THE LONG-TERM ACTION OF SODIUM FLUORIDE ON THE MOLECULAR-GENETIC MECHANISMS OF BONE TISSUE REMODELING - Жукова, Анна Геннадьевна; Семенова, Елена Александровна; Ядыкина, Татьяна Константиновна; Горохова, Лариса Геннадьевна; Бугаева, Мария Сергеевна (Medicine in Kuzbass, 2017)
Objective. Clinical and experimental study of the effects of the long-term action of sodium fluoride on the molecular-genetic mechanisms of bone tissue remodeling. Materials and methods. The mineral density of bone tissue has been studied, polymorphism of IL1B (rs1143634), IL6 (rs1800795) and CYP1A2 (rs762551) genes was determined in the workers of Novokuznetsk aluminum smelter. In the experiment, the change in the level of markers of bone tissue remodeling in the dynamics of fluoride exposure (osteocalcin, calcitonin, parathyroid hormone (PTH), C-terminal telopeptide (β-Cross Laps), alkaline and acid phosphatases) was studied. Results. Based on χ2 values, as well as the values of OR and P, the development of osteosclerosis in aluminum workers is statistically-valid associated with TT genotypes (χ2 = 4.11; OR = 2.60; P ≤ 0.05) for IL1B gene and has a positive associative relation with the genotype of GC (χ2 = 4.31; OR = 1.91; P ≤ 0.05) for IL6 gene. In the group of the patients with osteoporosis, statistically-valid association with the disease was detected for the genotype of CC gene responsible for the synthesis of the enzyme of the first phase of biotransformation of xenobiotics – CYP1A2. In an experiment, in the dynamics of fluoride exposure pathological bone tissue loss and the increase in the level of markers of its resorption were revealed: β-Cross-Laps – in 2.6 times, by 22 % – PTH and acid tartrate-stable acid phosphatase (APhts) activity in blood serum. Conclusions. It is shown that prolonged action of fluorides causes a change in the marker level of bone tissue remodeling. In the dynamics of sodium fluoride action, a pathological loss of bone tissue occurs due to excessive activation of osteoclasts.